PATRICIA: proof-of-concept implementation and validation of a real-time singing synthesizer - Brum, Leonardo A. Z.; Meneses, Eduardo A. L.; Moreno, Edward D. (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2025.13208, 2025)
This paper describes the implementation and validation process of PATRICIA, a proof-of-concept prototype of a system that performs real-time singing voice synthesis (SVS) for the Brazilian Portuguese language. A technological mapping was conducted to study the latest industrial developments in real-time SVS and give directions for PATRICIA design and implementation. The implemented architecture is described, and for the validation process, a series of video recordings of the system working was made as a musical demonstration. This demonstration was subjected to an evaluation by musical educators. A performance analysis with two CPU usage indicators was also performed on two different devices. The results of the validation are discussed and future enhancements are pointed out to overcome the current limitations of the system.